COMBATING INTRINSIC ANTIBIOTIC RESISTANCE IN GRAM-NEGATIVE BACTERIA - Taylor, Patricia (My University, 2011)
The current rise in multi-drug resistant Gram-negative bacterial infections is of particularconcern. Gram-negative pathogens are difficult to treat due to their intrinsic resistome.The outer membrane (OM) of Gram-negative bacteria serves as a permeability barrier tomany antibiotics, due in large part to the lipopolysaccharide (LPS) component that isunique to these organisms, and in addition to, the OM is lined with a number of multidrugresistant efflux pumps. As the clinical effectiveness of first line therapies declines inthe face of this resistance, novel strategies to discover new antibiotics are required. Theidentification of new antibiotic targets is one method currently being applied to meet thischallenge. This work examines the permeability barrier of Escherichia coli as a possibletarget for antibiotic adjuvants. A structure-function analysis of GmhA and GmhB, whichcatalyze the first and third conserved steps in LPS ADP-heptose biosynthesis, wasperformed. The active site residues of each of these enzymes were identified viacrystallographic, mutagenic, and kinetic analyses. Potential mechanisms have beenproposed, offering insight into the function of these potential adjuvant targets. In addition,a whole screen of E. coli was performed to identify compounds that potentiatenovobiocin, an antibiotic with limited activity against Gram-negative pathogens due toOM permeability. Four small molecules were found that were able to synergize withnovobiocin. One of these, A22, is known to alter bacterial cell shape, suggesting a newpathway for antibiotic adjuvants to combat Gram-negative infection. Together, thesestudies highlight the varied targets available for novel therapeutic strategies.
Keywords: High-throughput screening; enzymology; GmhA; GmhB; lipopolysaccharide; Gram-negative bacteria; Enzymes and Coenzymes; Medical Biochemistry; Enzymes and Coenzymes